Review and Reflection of JASAL Online Student Forum 2023 - Shiira Imada (Studies in Self-Access Learning Journal)
This report contains a review and my reflections on the Japan Association for Self-Access Learning (JASAL) student forum. The online forum was held on Saturday, June 10, 2023. Thirteen students and ten teachers, advisors, and members of JASAL staff from nine different universities met on Zoom. We had an opening session, three discussion sessions, and a closing session.